Faktor-Faktor yang Memengaruhi Continuance Intention Melalui E-Satisfaction Sebagai Variabel Intervening pada Aplikasi Tanda Tangan Digital (Studi Kasus PrivyID) - Nurul Faizah; Umi Widyastuti; Diena Noviarini (Teewan Journal Solutions, 2026)
This study aims to evaluate the effect of perceived ease of use, perceived value, and perceived security on continuance intention in the use of the PrivyID digital signature application, with e-satisfaction as an intervening variable. This study is motivated by the increasing adoption of digital signature technology in Indonesia, particularly PrivyID, which still faces challenges related to sustained usage. The research uses a quantitative approach with a survey method involving 125 PrivyID users. Data analysis was performed using SmartPLS 4 through the Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS). The results show that the three independent variables (perceived ease of use, perceived value, and perceived security) significantly affect e-satisfaction, which then mediates their effect on continuance intention. These findings emphasize that the level of user electronic satisfaction is a key factor in promoting the continued use of digital signature applications. This research contributes theoretically to the development of user behavior models in the context of financial technology, as well as providing practical implications for service providers like PrivyID to enhance user loyalty through optimizing user experience and service security.